Globalizations from below : understanding the spatialities, mobilities and resources of transnational migrant entrepreneurs across the globe - Riaño, Yvonne; Natasha A. Webster; Sandoz, Laure; Giacomo Solano; Sakura Yamamura (My University, 2024)
Transnational corporations have been long recognized as the building blocks of global system theory and their impact is widely acknowledged and studied. By comparison, we have insufficient understanding of transnational practices ‘from below’. We argue that focusing on transnational migrant entrepreneurship is a novel opportunity to gain insights into the social and economic processes of ‘globalization from below’. Such processes refer to the dynamics and practices initiated by actors outside the hegemonic socioeconomic spheres who, using various resources, move people, goods and ideas across national borders to create small-scale enterprises thus connecting distant places and people around the world. This special issue brings together a transdisciplinary group of researchers who examine the spatialities, mobilities and resources of transnational migrant entrepreneurs in Asia, Europe, North Africa, South America and the USA. The rich empirical base, coupled with diverse research methods, provides new insights into the phenomenon to scholars, policymakers and practitioners.
Keywords: Migrant entrepreneurship; transnationalism; globalization; spatialities; mobilities; resources; gender